Metallic NiPS3@NiOOH Core-shell Heterostructures as Highly Efficient and Stable Electrocatalyst for the Oxygen Evolution Reaction - Konkena, Bharathi; Masa, Justus; Botz, Alexander J.R. (Acs Catalysis, 2017)
We report metallic NiPS3@NiOOH core–shell heterostructures as an efficient and durable electrocatalyst for the oxygen evolution reaction, exhibiting a low onset potential of 1.48 V (vs RHE) and stable performance for over 160 h. The atomically thin NiPS3 nanosheets are obtained by exfoliation of bulk NiPS3 in the presence of an ionic surfactant. The OER mechanism was studied by a combination of SECM, in situ Raman spectroscopy, SEM, and XPS measurements, which enabled direct observation of the formation of a NiPS3@NiOOH core–shell heterostructure at the electrode interface. Hence, the active form of the catalyst is represented as NiPS3@NiOOH core–shell structure. Moreover, DFT calculations indicate an intrinsic metallic character of the NiPS3 nanosheets with densities of states (DOS) similar to the bulk material. The high OER activity of the NiPS3 nanosheets is attributed to a high density of accessible active metallic-edge and defect sites due to structural disorder, a unique NiPS3@NiOOH core–shell heterostructure, where the presence of P and S modulates the surface electronic structure of Ni in NiPS3, thus providing excellent conductive pathway for efficient electron-transport to the NiOOH shell. These findings suggest that good size control during liquid exfoliation may be advantageously used for the formation of electrically conductive NiPS3@NiOOH core–shell electrode materials for the electrochemical water oxidation.
Keywords: liquid exfoliation metallic NiPS3 nanosheets, oxygen evolution , NiPS3@NiOOH core−shell heterostructure, electrocatalysis